A scoping review of deictic gesture use in toddlers with or at-risk for autism spectrum disorder. (January 2018) - Manwaring, Stacy S; Stevens, Ashley L; Mowdood, Alfred; Lackey, Mellanye
Background and aims: Young children use deictic gestures, such as pointing, to indicate referents in their immediate environment. Early deictic gesture use is important in facilitating the development of language. In toddlers with or at-risk for autism spectrum disorder, the emergence and use of gestures may be delayed, and deficits in deictic gesture may inform clinical practice regarding early identification, differential diagnosis, and early intervention. The aim of this scoping review was to investigate the extent to which deictic gesture use has been examined in young children with or at-risk for autism spectrum disorder ≤ 36 months of age. Methods: Four databases (PubMed, PsycINFO, CINAHL, and ERIC) were comprehensively searched for relevant articles. Articles were reviewed in two phases: titles and abstracts followed by full text. Key variables related to participant/study characteristics and group differences on deictic gesture use were extracted. A narrative review was used to synthesize findings across studies. Main contribution: Nineteen studies met inclusion criteria – 12 studies of toddlers with autism spectrum disorder and 7 studies of high-risk infant siblings of children diagnosed with autism spectrum disorder. Overall, toddlers with autism spectrum disorder were found to demonstrate reduced gesture use across deictic gesture types and ages compared to those with typical development. Findings were more variable when comparing toddlers with autism spectrum disorder to those with other developmental delays and in high-risk infant sibling studies. Although only measured in a limited number of studies, results suggest differences in gesture use in toddlers with autism spectrum disorder based on communicative function. Conclusions: This review provides insight into the gesture use of toddlers with or at-risk for autism spectrum disorder. Results indicate the particular types of deictic gestures that may be delayed and the age ranges we might expect to observe these deficits in toddlers with autism spectrum disorder compared to those with typical development and other developmental delay groups. Results also reveal variability across studies in the measurement of gestures, and highlight where gaps remain in understanding deictic gesture use in young children with autism spectrum disorder. Implications: Findings have research and clinical implications related to profiling and targeting gesture use as part of the assessment and treatment process, including identifying patterns of strength and weakness in deictic gesture use of young children with or at-risk for autism spectrum disorder.